Formation and critical current densities of doped T1-1212 high temperature superconductors / Ahmad Kamal Hayati Yahya and Faizah Md. Salleh - Yahya, Ahmad Kamal Hayati; Md. Salleh, Faizah (2001)
Ti substituted TlSr-1212 type phase high-temperature superconductor with nominal starting composition Tlo.8Pbo.2Sr2-xTUCao.9Yo.iCu207 (x = 0-0.7) have been investigated. The normal state resistivity of the system showed metallic behavior for x < 0.5, semimetal-like behavior for x = 0.6 and semiconductor-like behavior for x = 0.7. Tlo.8Pbo.2Cao.9Yo.iCu207 was observed to superconduct with Tc onset of 90 K and Tc zero of 21 K. Substitution of Ti with x = 0.1 in place of Sr caused Tc zero to dramatically increase to 56 K. Further increase in Ti content (0.1<x< x < 0.7. The critical current density (Jc) measured around 20 K indicates maximum value of Jc at x = 0.3. The results were discussed in terms of changes in the valences of metallic ions and the optimum average Cu valence. The possible valence states of Ti in the Tl-1212 phase were also estimated. Results of structural investigations using x-ray diffraction are discussed.